Prioritizing green consumer purchasing attributes: an interpretive structural modelling methodology - KHARE, DR ASHISH; SHARMA, DR SUMEDHA (The journal of contemporary issues in business and government, 2021)
Protecting the environment and mother earth has assumed greater importance in the past few decades. Producers and consumers worldwide are making a radical shift towards green products, further adding remarkable value in the direction of sustainable economic development. The fact that the phenomenon of green consumer purchase is at a nescient stage in India shows that more research needs to be done in this area. This makes it crucial to understand and prioritize the attributes that lead to the purchase of green products. This study applies ISM methodology and provides a complex contextual relationship among characteristics through diagrammatic representation that enables marketers to precisely understand the consumer prioritization attributes at the time of green product purchasing. It highlights consumer insights and provides knowledge to the sellers about prime importance aspects, and act as a catalyst in the culmination of green purchase behaviour. This research is based on attributes classified through the literature survey followed by an expert panel discussion.